Solidaritas Organisasi Muslimah Masjid Agung Ibnu Batutah di Nusa Dua, Bali - Laila, Fina Yulfa; Nugroho, Wahyu Budi; Kamajaya, Gede (JURNAL ILMIAH SOSIOLOGI: SOROT, 2023)
This research focuses on the phenomenon muslimah Masjid Agung Ibnu Batutah (Musmaiba) in Nusa Dua, Bali. The purpose of this study is to explain the social impact of Musmaiba's solidarity on members and the surrounding community. The method used in this study is a qualitative approach with a descriptive-narrative type. The theory chosen as a scalpel in analyzing this research is social solidarity from Emile Durkheim. The results of this study revealed that there were several programs organized by Musmaiba including tahsin al-Quran, recitation of women's fiqh, monthly routine activities, fostering orphans and duafa, cooperatives, social gatherings, social visits and nursing corpses. There are two impacts from Musmaiba's solidarity, namely the socio-cultural impact and the socio-economic impact. Then, the factors that form social solidarity in Musmaiba include low division of labor, strong collective awareness, the applicable law is religious law, low individuality, and quite diverse community specializations. Solidarity that is formed does not make this organization primordial, Musmaiba has an open attitude to people of other religions. Based on the analysis that has been carried out, the author views that the social impact of Musmaiba's social solidarity cannot be separated from the family relationships they have built. This relationship creates an attitude of maintaining and perpetuating values, caring for each other, and the drive to mutually prosper each other.